Late Effects and Survivorship Issues in Patients with Neuroblastoma - Danielle Novetsky Friedman; Tara O. Henderson (MDPI AG, 2018)
Over the past two decades, marked progress has been made in understanding the biology of neuroblastoma; this has led to refined risk stratification and treatment modifications with resultant increasing 5-year survival rates for children with neuroblastoma. Survivors, however, remain at risk for a wide variety of potential treatment-related complications, or “late effects”, which may lead to excess morbidity and premature mortality in this cohort. This review summarizes the existing survivorship literature on long-term health outcomes for survivors of neuroblastoma, focusing specifically on potential injury to the endocrine, sensory, cardiovascular, pulmonary, and renal systems, as well as survivors’ treatment-related risk for subsequent neoplasms and impaired quality of life. Additional work is needed to assess the potential late effects of newer multimodality therapies with the aim of optimizing long-term medical and psychosocial outcomes for all survivors of neuroblastoma.